Predictive Modeling the Turbidity Response in Al-Saray Water Distribution Network in Najaf Governorate/Middle of Iraq, Using PODDS Model - Abed Zahraa H.; Jasem Hayder M.; Mohammed Hayder S. (Civil and Environmental Engineering)
Reducing water turbidity is one of the main issues the water industry is currently experiencing. The ability to predict the spatial probability and intensity of discoloration events in distribution systems can lead to the adoption and improvement of proactive operation and maintenance strategies to reduce turbidity. The main objective of this study is to forecast Using the Prediction of Discoloration in Distribution Systems (PODDS model), simulate the turbidity response in the Al-Saray water distribution network caused by higher flow rates and a change in the daily demand pattern for water consumption. The work covered AL -Saray water distribution network. with took into account the two feed flowrate (FFR) values of the AL-Saray water network, which were (522 and 5870) m3/day. The turbidity response was observed to be low when daily flows were supplied to the network, but it increased as the flow increased. The maximum turbidity response was observed when water was fed into the Al-Saray water network at a flowrate of 5780 m3/day. the material layers are conditioned to daily flow, or shear stress. However, when the flow increases due to an increased demand for water, the fluid’s shear stress exceeds the material layers’ shear strength, which leads to the material becoming mobilized.